IKON, INDEKS, DAN SIMBOL BUDAYA INDRAMAYU DALAM KARYA-KARYA KEDUNG DARMA ROMANSHA - Agung Joyo Mulyono; Setya Yuwana Sudikan; Ririe Rengganis (Universitas Wiralodra, 2023)
This article discusses the icons, indexes, and cultural symbols of Indramayu in Kedung Darma Romansha's works in the form of short stories, poetry and novels, totaling five books, namely: (1) Kelir Slindet, (2) Telembuk Dangdut dan Kisah Cinta yang Keparat, (3) )Rab(b)i, (4)Rahi(i)m, and (5)Tarling Dangdut Diva Pantura. The approach in this study uses semiotics as an approach to a literary work, while these works will be analyzed using the theory of icons, indexes and symbols. Indramayu's cultural icons in his prominent works are found in the words, TKW, RCTI, PSK, and Mango. Indramayu's cultural index is often seen in his work because of the Third Prey which weakens the economy, prostitutes, and unusual household life. While the cultural symbols of Indramayu in his work, there are several that often appear in the beliefs of the people of Indramayu in mysticism, reflected in the scientific terms